Excellence in business communication - John V. Thill (Prentice-Hall, 1997)
The book covers all the basic principles and presents them in a traditional sequence. It offers business communication experience through real-world simulations featuring actual companies, engaging writing style, and eye-opening graphics all bringg the subject to life, capturing the essence of business communication